MSMEs DEVELOPMENT MODEL IN THE FAST-FOOD SECTOR THROUGH SOCIAL INNOVATION AND BUSINESS MANAGEMENT IN IMPROVING COMMUNITY WELFARE - Nada Kusuma; Muh. Husriadi; Hisna (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
MSME sector fast food​ has a strategic role in the economy national However Still face challenge in the form of limited product innovation, suboptimal business management and low access to training as well as mentoring. This study aims to developing a model for empowering fast food MSMEs through integration of social innovation and business management to improve competitiveness and welfare society. The research method used is qualitative with a case study approach, data collection through interview in-depth, observation participatory and documentation on MSME actors in several sub-districts in Kendari City. The results of the study showed that product development innovative, collaboration community, as well as implementation systematic business management capable increase capacity adaptation, efficiency operational, and market access for MSMEs. Continuous training and mentoring have also proven to be strengthen skills managerial and expanding Network effort. The implications of this research confirm the importance of empowerment models holistic that combines social and business aspects as well the need support digital technology policies and facilitation to ensure sustainability and inclusiveness of fast food MSME development.